No magic tricks: commodity, empowerment, and the sale of StreetWise in chicago - McGill, Kenneth (Journal of Linguistic Anthropology, 2013)
Use-value and exchange-value are pragmatic features of commodity exchange which are apparent from the careful study of specific interactions, as well as from the viewpoint of economic processes at large. While Marx's well-known attempt to describe this pair of concepts in Capital (2001) takes the latter tack, I attempt here to take the formeri.e., to approach the composition of the commodity from the point of view of the pragmatics of interaction. In doing so, I offer a semiotic model of the valuation of commodities which differs from accounts given by Kockelman (2006) and Agha (2011). The ethnographic object at stake in this essay is StreetWise, a Chicago street newspaper said to have empowering effects on its vendors.
Keywords: Commodity; Empowerment; Street newspapers; United States; Value; dept.ant